A case report of typhoid perforation of the ileum - Ertuğrul, Meliha; Özdöl, Güven; Büyükpamukçu, Nebil (The Turkish Journal of Pediatrics, 1975)
A case of typhoid fever with perforation of the gut is presented which has been reported only rarely in recent years. In this patient the condition was correctly diagnosed and he was operated on in time; the patient made an uneventful recovery in a short time.